A novel molecularly imprinted electrochemical sensor based on graphitic carbon nitride nanosheets decorated bovine serum albumin@MnO2 nanocomposite for zearalenone detection - Rehman, Nesrin Çapar; Özdemir, Neslihan; Boyacıoğlu, Havva; Yola, Mehmet Lütfi; Yola, Mehmet Lütfi (Academic Press Inc.)
Zearalenone (ZEA), as a carcinogenic mycotoxin, is widely found in a wide variety of food products such as grains and its carcinogenicity, neurotoxicity, and estrogenic effects on humans were reported. In this report, a novel electrochemical sensor based on graphitic carbon nitride nanosheets decorated bovine serum albumin@MnO2 (g-C3N4NS/BSA@MnO2) nanocomposite and molecularly imprinted polymers (MIPs) was developed and applied to rice samples for ZEA determination. Firstly, the synthesis of bulk g-C3N4 by thermal poly-condensation method was completed. After the ultra-sonication treatment of bulk g-C3N4 providing graphitic carbon nitride nanosheets, the nanocomposite was successfully produced via electrostatic forces between g-C3N4NS and BSA@MnO2. Then, a novel MIP-based electrochemical electrode including g-C3N4NS/BSA@MnO2 was prepared in the presence of ZEA as target analyte and pyrrole (Py) monomer by cyclic voltammetry (CV). The formed electrochemical sensor exhibited a linearity of 1.0 – 10.0 ng L−1 with a detection limit (LOD) of 0.25 ng L−1. Furthermore, the high selectivity, reproducibility and stability of the prepared MIPebased electrochemical sensor exhibited that it could be used in real sample analysis such as rice. © 2023 Elsevier Inc.
Keywords: Graphitic carbon nitride; Molecularly imprinting; Rice analysis; Zearalenone